Individual Education Plan Considerations for Online Learning: Accommodations - Berenson, Carolyn L. (Journal of the American Academy of Special Education Professionals, 2020)
This article provides guidance for including students with disabilities (SWDs) in online learning. Federal special education law and research are currently outpaced by practice as students with disabilities participate in K-12 online learning in increasing numbers. While online learning has the flexibility to present content in multiple ways and to offer students multiple means for expression, IEP accommodations assigned to onground learning are often incongruent with online learning. Accommodations should be reconsidered for online learning by delineating learning profile skill deficits and filtering them through three lenses that characterize important features of online learning: synchrony in computer-mediated communication (CMC); World Wide Web (web) and technology; and curriculum.